Emitter Discharge Sensitivity to Water Temperature - Thokai, R T; Mokashi, A K; Kumar, S Ramesh; Shindhe, Y R (Annals of Arid Zone, 2016)
The nozzle type' emitters of rated discharge 4 L h-1 and 8 L h·1 with Pressure Compensating (PC) and Non-Pressure Compensating (NPC) mechanisms and four different diameter microtube emitters, ranging from 1.20 to 1.77 mm, were tested in a laboratory to determine the sensitivity of their flow rates to temperature variation. Thc sensitivity of emitter dischargc to temperature was determined for water temperature ranging from 20°C to 60°C (68°F to 140°F) at a line pressure of 1.00 kg cm-2 for emittcrs and 0.6 kg cm-2 for microtubes. The discharge rates ranging from 6.842 L h·1 to 7.6293 L h-1 wcre observed in different diameter microtubes. The experimental results indicated linear relationship of emitter and microtube dischargcs at various water temperatures at a given line pressure. The percentage discharge variation ranging from 53 to 56% with' relative flow rate increase at a constant rate of 1.56% per 0c. was obscrved for all microtube emitters tested, irrcspective of their diameters in the water temperature range of 20 to 60°C. The discharge variation was observed to be 4.62%, with a maximum relative discharge ratc increase of 0.115% per °C for NPC emitters whereas for PC emitters, these wcre 1.53% and 0.038% per °C in the same range of water temperature, respectively. The design consideration should, therefore, include temperature-induced discharge variations to cnsure uniformity of water application.